An in vitro assay for detection of glomerular binding IgG autoantibodies in patients with systemic lupus erythematosus. - Budhai, L (1996)
The deposition of anti-dsDNA antibodies in the glomerulus is believed to play a critical role in the pathogenesis of nephritis in SLE. However, an absolute correlation between serum levels of anti-dsDNA antibodies and renal disease has not been found. Recently a glomerular binding assay (GBA) has been developed to detect IgG binding to isolated rat glomeruli. We have used the GBA to study sera from four groups of SLE patients: (A) + anti-dsDNA antibodies, active nephritis; (B) - anti-dsDNA antibodies, active nephritis; (C) + anti-dsDNA antibodies, no nephritis; and (D) - anti-dsDNA antibodies, no nephritis. The serum anti-dsDNA antibodies in group A and group C patients could not be distinguished on the basis of isotype, charge, or cross-reactivity with histones. Nevertheless, the mean intensity of glomerular immunofluorescence was significantly higher in group A than in the three other patient groups and distinguished between patients with serum anti-dsDNA antibodies who had nephritis and those without clinically apparent nephritis. GBA reactivity was unaffected by DNase treatment of sera, but was partially inhibited by preincubation with dsDNA. These findings are consistent with the hypothesis that some anti-dsDNA antibodies cross-react with glomerular components and that the presence of this cross-reactivity is associated with, and may be responsible for, the development of nephritis. In addition, we have identified a group of SLE patients with renal disease and typical renal histopathology and immune deposits who do not have serum anti-dsDNA antibodies or antibodies that directly bind to glomeruli in the GBA. The mechanism of renal immune deposition in these patients remains to be determined.